2022
DOI: 10.5334/ijic.6419
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Integrated Care for the Aged Population in Anhui and Fujian Province of China: A Qualitative Study

Abstract: Introduction: Implementing integrated care for the aged population has been regarded as a mechanism to achieve healthy ageing. However, evidence from undeveloped nations has been scant. This study aims to explore the integrated care experience in Anhui and Fujian Province of China based on the Rainbow Model of Integrated Care (RMIC). Methods: The qualitative study was conducted in Anhui (in the middle area) and Fujian Province (in the eastern area) between May and Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The MCCs can harm the physical and mental health of the elderly, with the impact increasing as the degree of MCCs increases [ 39 , 40 ]. FDCSs were helpful to improve the treatment effect of chronic diseases, improve the quality of comprehensive care, and improve the health-related quality of life [ 7 , 9 , 41 , 42 ]. Patients with chronic diseases may also be more willing to use health services to meet their health needs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCCs can harm the physical and mental health of the elderly, with the impact increasing as the degree of MCCs increases [ 39 , 40 ]. FDCSs were helpful to improve the treatment effect of chronic diseases, improve the quality of comprehensive care, and improve the health-related quality of life [ 7 , 9 , 41 , 42 ]. Patients with chronic diseases may also be more willing to use health services to meet their health needs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FDCSs have a positive effect on residents' health. Yuan et al showed that family doctors can provide high-quality comprehensive care services for the elderly [ 7 ]. The study of Yu et al and Wang et al showed that contracted residents strengthened the monitoring of chronic diseases and increased the utilization of primary care facilities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies explore how the government should optimize this policy from the perspective of policymakers. 12 For example, based on the experience of home elderly care in Japan, some research suggests that China should actively promote long-term care insurance and integrate elderly care service and chronic disease management services. 13 2.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have been conducted at a strategic macro or national level, focusing on health system and policy implementation. For instance, they have examined integrated care policy implementation [ 23 , 24 , 25 ], primary care, delivery systems, and care coordination at the organizational level [ 26 , 27 ]. However, as highlighted in a review study, the majority of research focuses on coordinating care at the clinical (micro) level and service/organizational (meso) level, with limited exploration of system (macro) level integration and multilevel integrated care approaches [ 28 ].…”
Section: Introductionmentioning
confidence: 99%